Positive data circulation established by Kyushu Smart Fisheries (QSF) team - Hirose, Naoki; Takikawa, Tetsutaro; Ito, Takeshi; Nagamoto, Atsushi; Takagi, Nobuo; Kokubo, Takayuki; Kimura, Mikiya; Yabuki, Takashi; Hazama, Takuto (Frontiers in Marine Science, 2024)
Subsurface observations in coastal and shelf seas remain insufficient compared to profiling measurements in open oceans. To address this gap, we have developed a system that involves coastal fishermen in conducting in-situ measurements. By assimilating this observation data in real-time, we can provide valuable feedback on ocean predictions to support their fishing activities. We adapted the traditional full-scale conductivity-temperature-depth (CTD) instrument into a more conventional model dedicated to small-scale fisheries. This simple and smart CTD device allows Bluetooth communication with Android devices. Although its accuracy and pressure resistance were reduced to make it affordable, it remains effective for our data assimilation purpose. Along with acoustic current data, the accuracy of coastal ocean prediction models, particularly for velocity components, can be significantly increased. Using the intuitive and user-friendly forecasting app, cooperating fishermen have been able to reduce fuel usage, working hours, and gear damages, thereby improving profitability and working conditions. This app has become an indispensable operational tool for fishermen in the Kyushu region, motivating them to actively participate in coastal ocean observations.